Implementation of Quality Management Practices and Firm’s Innovation Performance: Mediation of Knowledge Creation Processes and Moderating role of Digital Transformation - Butt, Sadia; Yazdani, Naveed (Pakistan Journal of Humanities and Social Sciences, 2023)
Presently, Industry 4.0 (I4.0) revolution is transforming operations and businesses of organizations through technological advancements.These digital technologies are hugely impacting the technological innovations (TIs) and execution of total quality management (TQM) in the organizations. Existent literature on TQM and firm’s innovation performance (IP) relation has shown mixed findings exclusively, in manufacturing companies. Desptie strategic significance of both TQM and innovation (INN) to improve sustainable competitive gain, this is an under-researched area in I4.0 context. Additionally, the Quality 4.0 is also new concept and role of I4.0 tchnologies in transformation of trational TQM function hasn’t been researched so far. Despite strategic significance of role of knowledge creation processes (KCPs) towards firm’s IP and performance in I4.0, there is dearth of research addressing integrative framework TQM, KC and IP exclusively in progressing country context. Considering these prevailing gaps in literature, current study is an attempt to develop and test a model in context of Pakistan in relevance to I4.0. The proposed framework examines the influence of executing quality management or QM practices (QMP) on innovation performance (IP). Additionally, mediating role of knowledge creation processes (KCPs) and moderation of digital transformation (DIT) is also explored in QMP-IP relation. Data of 265 respondents were obtained from ISO 9001 certified manufacturing firms of Pakistan through structured questionnaire on Likert Scale. Data were analysed through SPSS 23.0 and Hayes process macro applying statistical tests (reliability, correlation, and regression analysis). Study results revealed that all variables were positively correlated. Quality management practices (QMP) had positive and significant impact on firm’s IP. Results supported partial mediation effect of organizational knowledge creation processes (KCPs) in QMP-IP relationship. While, moderating impact of digital transformation (DIT) in QMP-IP relation was also supported. Study findings has implications for both and academia, management and practitioner. This study contributes to prevalent literature as it empirically tests a proposed framework to address under-researched area of QMP- IP relation in relevance to DIT and KCPs in Pakistan context and I4.0.